PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, OPINI AUDIT DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Yohanes Baptista Tupen Ebang; Syaikhul Falah; Bill J.C Pangayow (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This study aims to analyze the effect of company size, profitability, solvency, audit opinion and the size of the public accounting firm on audit delay in manufacturing companies listed on the Indonesia StockExchange. The analysis was carried out using multiple linear regression analysis, where the classical assumption test was carried out first, the analysis tool using SPSS 21. The observation period in this study was 2016-2018 using a sample of 36 selected manufacturing companies based on purposive sampling with a total of 108 samples overall during 3 years of observation. The results of this study indicate that the average audit delay in manufacturing companies in 2016-2018 is 78.28 days. The results showed that the variable size of the company, profitability, solvency, audit opinion and the size of the public accounting firm did not affect audit delay. However, the independent variables simultaneously influence the dependent variable.